2000
DOI: 10.1038/79766
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP is essential for mouse thymocyte differentiation and TCR signaling

Abstract: The Ras signaling pathway plays a critical role in thymopoiesis and T cell activation, but the mechanism of Ras regulation is controversial. At least one mode of Ras regulation in T cells involves the messenger diacylglycerol (DAG). RasGRP, a Ras activator with a DAG-binding C1 domain, is expressed in T cells and thymocytes. Here we show that thymi of RasGRP-null mutant mice have approximately normal numbers of immature thymocytes but a marked deficiency of mature, single-positive (CD4+CD8- and CD4-CD8+) thymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
464
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(486 citation statements)
references
References 37 publications
21
464
0
1
Order By: Relevance
“…Accordingly, positive selection is also attenuated in mice deficient in CD3␦ and biochemical analysis revealed that ERK activation is severely impaired in these mice (11). Recent evidence has also shown that a novel guanine nucleotide exchange factor for Ras, RasGRP, is involved in thymocyte-positive selection (12). These studies along with studies using pharmacological inhibitors of the ERK pathway (13)(14)(15) clearly support the role for ERK during positive selection.…”
mentioning
confidence: 57%
“…Accordingly, positive selection is also attenuated in mice deficient in CD3␦ and biochemical analysis revealed that ERK activation is severely impaired in these mice (11). Recent evidence has also shown that a novel guanine nucleotide exchange factor for Ras, RasGRP, is involved in thymocyte-positive selection (12). These studies along with studies using pharmacological inhibitors of the ERK pathway (13)(14)(15) clearly support the role for ERK during positive selection.…”
mentioning
confidence: 57%
“…They also increased their expression of prostaglandin D 2 synthase Ͼ100-fold (22). T cells express RasGRP1, and targeted disruption of this GEF's gene in mice results in a marked deficiency of mature CD4 ϩ /CD8 Ϫ and CD4 Ϫ /CD8 ϩ T cells (23). In a similar manner, it now appears that RasGRP4 regulates the final stages of MC differentiation and maturation, including what protease and lipid mediators MCs produce.…”
mentioning
confidence: 71%
“…The 3T3 cell line was examined because this fibroblast line was used in the transfection experiments noted below to evaluate the role of mRasGRP4 in cellular adherence and activation of H-Ras. Finally, the T cell hybridoma was examined because mRasGRP1 was cloned from a T cell hybridoma and because this GEF is essential for T cell development and function in the mouse (23,26).…”
Section: Tissue Distribution Of the Mrasgrp4 Transcriptmentioning
confidence: 99%
“…27,33 Some functions for GEFs in the immune system have been described. RasGRP is important to mouse thymocyte differentiation after TCR stimulation, 34 and members of Vav family are essential for response of B lymphocytes to LPS. 35 Numerous studies with tumour cell lines, such as Jurkat cells or EL4 mouse lymphoma cells, indicate that Ras represents an essential link between TCR stimulation and cellular proliferation or cytokine gene induction.…”
Section: Discussionmentioning
confidence: 99%